Health‐related guilt in chronic primary pain: A systematic review of evidence. Issue 1 (5th May 2021) - Serbic, Danijela; Evangeli, Michael; Probyn, Katrin; Pincus, Tamar
Abstract : Purpose: Chronic primary pain conditions are characterized by significant functional disability, emotional distress, and diagnostic uncertainty. Health‐related guilt associated with coping and living with chronic pain is poorly understood. There had been no attempts to synthesize findings on health‐related guilt across studies. Therefore, the aim of this study was to conduct a systemic review of evidence, to enable an understanding of the role of health‐related guilt in chronic primary pain, and to provide directions for future research. Method: A search strategy was developed based on our eligibility criteria. Four databases (PsycINFO, Scopus, PubMed, and Web of Science) were searched for relevant papers from inception to 8 July 2020. Data from 12 qualitative and six quantitative studies were synthesized narratively. Results: The review of qualitative studies resulted in three themes, relating to the management of pain, diagnostic uncertainty/legitimizing pain, and how participants' actions or inactions affect others. These findings were integrated with evidence from quantitative studies, which showed that higher levels of guilt were associated with more pain and pain interference, functional impairment, and poorer psychological and social functioning. Conclusions: The findings demonstrate that health‐related guilt is an important psychological factor associated with more pain and poorer function in people with chronic primary pain conditions. Future research should examine health‐related guilt as a potential mediating/moderating factor leading to more distress and suffering in this population and as a potential target for interventions.